2022
DOI: 10.3390/agronomy12123168
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Factors Affecting C-N Fractions and Yield of Paddy Soils by Total Straw Return and N Fertilizer Application

Abstract: The effective use of nutrient-rich crop straw is an important way to use resources efficiently and to sustain agricultural development. This meta-analysis study collected and analyzed the data of 6788 observations published in 238 peer-reviewed papers to investigate differences in soil C-N fractions and yields of paddy soils under different straw-return amounts. This large dataset was also used to quantify the degree of influence of factors such as climate characteristics, soil properties, N fertilizer applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…One common practice in agricultural production worldwide is the return of straw to the soil, which significantly enhances the soil environment, soil fertility, and, consequently, crop yields [5]. Numerous studies have demonstrated the positive impact of returning straw on soil fertility, soil structure, water retention, and the soil microbial environment, ultimately leading to increase crop yields [6][7][8][9][10]. Studies by Wang et al have shown that the combined application of nitrogen fertilizer and straw returning improved soil nutrient status, cotton canopy photosynthetic capacity, seed cotton yield, and nitrogen utilization efficiency [11].…”
Section: Introductionmentioning
confidence: 99%
“…One common practice in agricultural production worldwide is the return of straw to the soil, which significantly enhances the soil environment, soil fertility, and, consequently, crop yields [5]. Numerous studies have demonstrated the positive impact of returning straw on soil fertility, soil structure, water retention, and the soil microbial environment, ultimately leading to increase crop yields [6][7][8][9][10]. Studies by Wang et al have shown that the combined application of nitrogen fertilizer and straw returning improved soil nutrient status, cotton canopy photosynthetic capacity, seed cotton yield, and nitrogen utilization efficiency [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, meta-analysis has been more and more widely used in the field of agronomy in China, and as a statistical tool of larger spatial and temporal scales, it continues to play a unique and important role [36][37][38]. Some scholars have used meta-analysis to unite several independent and relevant studies to analyze the general trend of the effects of drought stress on winter wheat [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, nitrogen fertilizer can be used to effectively regulate the C/N ratio after straw is returned to a field. This helps improve microbial activity ( Zhang et al, 2022 ; Surigaoge et al, 2023 ), promote straw decomposition, and provide sufficient nitrogen fertilizer for crops. Previous studies have primarily focused on the effect of common urea fertilizer on straw decomposition ( Liu et al, 2021 ; Mühlbachová et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%